Speed responses of trucks to light and weather conditions. Issue 1 (1st January 2019) - Jägerbrand, Annika K.; Sjöbergh, Jonas
Abstract: Light conditions are essential factors in traffic safety, but the relationship between light conditions and vehicle speed is not fully understood and has rarely been examined for trucks. We asked the following questions: I) if vehicle speed between brighter and darker conditions in clear weather will be different? II) if vehicle speeds are lower during rain and snow than in clear weather conditions? and if so III) if the speed reduction in rainy and snowy weather conditions is more substantial on roads without road lighting in darkness? We investigated how the speed of trucks was affected by weather conditions (clear, rain, and snowfall), daylight, darkness, and road lighting by using traffic and weather data from 25 locations on the Swedish road network. Seventeen of the 25 locations were roads with road lighting. Speed responses by 5, 344, 287 vehicle passages by trucks was included in the analyses, more specifically 3, 659, 940 passages by light-duty vehicles and 1, 684, 347 passages by heavy-duty vehicles. The data was extracted from hourly measurements for the period 2012-09-01 to 2014-05-31. No evidence of consistent patterns of speed differences with respect to lighting conditions (darkness, daylight, twilight or road lighting) under clear weather conditions were detected. Truck speeds decreased in response to snowfall, but not to rain, with the decrease dependant on the amount of snow. Effects of road lighting on speed reduction in rainy and snowy weather was not shown.